Предмет: Математика,
автор: angelinagirl17
(y-3)•3,2+1,2(2y+8)=0
Ответы
Автор ответа:
1
3,2(y-3) + 1,2(2y+8) = 0
3,2y - 9,6 + 2,4y + 9,6 = 0
5,6y = 0
y = 0
3,2y - 9,6 + 2,4y + 9,6 = 0
5,6y = 0
y = 0
Автор ответа:
1
Ответ:
Пошаговое объяснение:
(y-3)·3,2+1,2(2y+8)=0 |×5/2
8y-24+6y+24=0
14y=0; y=0
Похожие вопросы
Предмет: Русский язык,
автор: галка7
Предмет: Английский язык,
автор: dumov04
Предмет: Русский язык,
автор: mbi2002
Предмет: Русский язык,
автор: malbergv484
Предмет: Русский язык,
автор: max20182